ANALISIS KEPUASAN PASIEN BPJS DALAM PELAYANAN KESEHATAN - Sutiswa, Shandra Isasi; Arniawan, Arniawan; Kuntoadi, Gama Bagus; Putra, Ryryn Suryaman Prana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Patient satisfaction is a customer response to fulfilling needs and expectations. The Rambah Samo I Puskesmas is one of the Puskesmas in Rokan Hulu Regency which has experienced a decrease in the number of patient visits utilizing services. The purpose of the study was to determine the relationship of several factors with patient satisfaction with primary health services. Quantitative research type with cross sectional design. The research was conducted in 2023 with a sample of 99 people. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between reliability (p value 0.043), responsiveness (p value 0.040, POR 2.751). It is recommended to the Puskesmas to be able to improve the quality of health services consisting of administrative officers, health worker services, and pharmacy services in order to provide friendly and attentive service to patients and provide clear information to patients.Keywords: Reliability, Patient, Health Center